Polypropylene/lignin blend monoliths used as sorbent in oil spill cleanup. Issue 9 (September 2020) - Alassod, Abeer; Gibril, Magdi; Islam, Syed Rashedul; Huang, Wanzhen; Xu, Guangbiao
Abstract: With increasing industrial development, frequent oil spillages in water; therefore, it is imperative and challenging to develop absorbents materials that are eco-efficiency, cost-effective, and pollution prevention. In this study, sorbents obtained from Lignin incorporated with Polypropylene in different levels loading 0, 10, 20 % wt using thermally induced phase separation Technique (TIPS). The Polypropylene/Lignin blend monoliths were fabricated and compared in terms of morphological, thermal, and wetting characterizations. The successfully blending of different lignin concentrations with preserved the chemical structure of the polymer was confirmed by FTIR analysis. Thermogravimetric tests displayed that the existence of Lignin has changed the onset temperature (Tonset) of the blending sorbents, decreasing as the loading of Lignin is increased. The contact angle measurement showed a decrease in the hydrophobicity of sorbents with increasing lignin loading, Polypropylene/Lignin blend monoliths showed better absorption toward oils (soybean – engine) as compared to Polypropylene itself. PP10L showed an improvement in the oil sorption capacity around 2 times compared to the Polypropylene. These excellent features make Polypropylene/Lignin blend monoliths more competitive promising candidates than commercial absorbent. Abstract : Temperature; Lignin; Wettability; Hydrophobicity; Thermal properties; Pollution; Engineering; Materials science; Environmental science.